A ratiometric, fluorometric approach for surface charge mapping of biosilica features. Issue 23 (9th November 2022) - Parambath, Mithun; Fayyaz, Aneeqa; Efimov, Igor; Hanley, Quentin S.; Perry, Carole C.
Abstract : We describe a surface charge imaging method for heterogeneous biosilicas based on relationships between zeta (ζ) potential, feature size of nanoparticles, and PDMPO fluorescence and apply it to silicified structures from living organisms. Abstract : We describe a surface charge imaging method for heterogeneous biosilicas based on relationships between zeta ( ζ ) potential, feature size of nanoparticles, and PDMPO fluorescence and apply it to silicified structures from plants and diatoms. The methodology provides the first opportunity to map the surface charge of large heterogeneous biosilica materials and indicates that local surface charge is related to morphology below the diffraction limit ( ca. 20–130 nm) with sharper features showing less negative zeta potential equivalent surface charge suggesting that the zeta potential of silica structures can be adjusted by engineering surface morphology. We show that the approach can be used to study living silicified biological tissues without recourse to sectioning and fixation. Further, the approach could be used for the study of other metal oxides possessing hydroxylated moieties. The method has potential to open up opportunities for the engineering of materials with defined charge characteristics for the solution of biomedical engineering problems including materials for tissue replacement.